Host-Induced Gene Silencing of a Multifunction Gene Sscnd1 Enhances Plant Resistance Against Sclerotinia sclerotiorum - Ding, Yijuan; Chen, Yangui; Yan, Baoqin; Liao, Hongmei; Dong, Mengquan; Meng, Xinran; Wan, Huafang; Qian, Wei (Frontiers in Microbiology, 2021)
Sclerotinia sclerotiorum is a devastating necrotrophic fungal pathogen and has a substantial economic impact on crop production worldwide. Magnaporthe appressoria-specific (MAS) proteins have been suggested to be involved in the appressorium formation in Magnaporthe oryzae. Sscnd1, an MAS homolog gene, is highly induced at the early infection stage of S. sclerotiorum. Knock-down the expression of Sscnd1 gene severely reduced the virulence of S. sclerotiorum on intact rapeseed leaves, and their virulence was partially restored on wounded leaves. The Sscnd1 gene-silenced strains exhibited a defect in compound appressorium formation and cell integrity. The instantaneous silencing of Sscnd1 by tobacco rattle virus (TRV)-mediated host-induced gene silencing (HIGS) resulted in a significant reduction in disease development in tobacco. Three transgenic HIGS Arabidopsis lines displayed high levels of resistance to S. sclerotiorum and decreased Sscnd1 expression. Production of specific Sscnd1 siRNA in transgenic HIGS Arabidopsis lines was confirmed by stem-loop qRT-PCR. This study revealed that the compound appressorium-related gene Sscnd1 is required for cell integrity and full virulence in S. sclerotiorum and that Sclerotinia stem rot can be controlled by expressing the silencing constructs of Sscnd1 in host plants.